2022
DOI: 10.3390/biomedicines10061272
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of NLR, MLR, and PLR in the Outcome of End-Stage Kidney Disease Patients

Abstract: Background: Chronic kidney disease (CKD) is a global public health problem with a high mortality rate and a rapid progression to end-stage kidney disease (ESKD). Recently, the role of inflammation and the correlation between inflammatory markers and CKD progression have been studied. This study aimed to analyze the predictive value of the neutrophil–lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), and platelet-to-lymphocyte ratio (PLR) in assessing the outcome of ESKD patients. Methods: A retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 57 publications
2
50
0
Order By: Relevance
“…Apart from well-known biomarkers of inflammation such as C-reactive protein, interleukin-6 (IL-6), and procalcitonin, hematological indices have gained popularity in recent years in the specialized literature due to their inexpensive cost and performance [ 7 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 38 , 39 , 40 , 41 ]. Moreover, hematological indices such as neutrophil-lymphocyte ratio (NLR), monocyte-lymphocyte ratio (MLR), systemic immune inflammation index (SII), Systemic Inflammation Response Index (SIRI), and Aggregate Index of Systemic Inflammation (AISI), have been applied to predict the prognosis in patients with the cardiovascular disease [ 42 , 43 , 44 ], acute limb ischemia [ 45 , 46 ], chronic kidney disease [ 47 , 48 ], peripheral artery disease [ 49 ], malignancy [ 50 , 51 , 52 ], and more recently in the case of COVID-19 patients [ 7 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from well-known biomarkers of inflammation such as C-reactive protein, interleukin-6 (IL-6), and procalcitonin, hematological indices have gained popularity in recent years in the specialized literature due to their inexpensive cost and performance [ 7 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 38 , 39 , 40 , 41 ]. Moreover, hematological indices such as neutrophil-lymphocyte ratio (NLR), monocyte-lymphocyte ratio (MLR), systemic immune inflammation index (SII), Systemic Inflammation Response Index (SIRI), and Aggregate Index of Systemic Inflammation (AISI), have been applied to predict the prognosis in patients with the cardiovascular disease [ 42 , 43 , 44 ], acute limb ischemia [ 45 , 46 ], chronic kidney disease [ 47 , 48 ], peripheral artery disease [ 49 ], malignancy [ 50 , 51 , 52 ], and more recently in the case of COVID-19 patients [ 7 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has reported that NLR, MLR, and SIRI, are prognostic indicators in several malignancies [ 20 ]. Given that systemic inflammatory responses participate in multiple diseases other than cancer, a growing body of literature has proposed that NLR, MLR, and SIRI, can also be potential predictors of various diseases, including peripheral arterial disease (PAD) [ 21 ], mortality after coronary artery bypass surgery [ 22 ], outcomes of target vessel restenosis after infrainguinal angioplasty [ 23 ], and end stage renal disease (ESRD) [ 24 , 25 ]. However, very few studies have focused on the role of systemic inflammatory responses in the formation of kidney stones [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in our research we used simple and non-invasive methods to calculate cellular indicators of inflammation, such as NLR, dNLR, MLR and the hypercoagulable state (PLR) for all groups of DBDs [ 9 ]. These ratios are correlated with poor prognosis in a variety of conditions, including end-stage kidney disease, heart disease and cancer [ 10 ]. Previous studies have shown there is a relationship between high NLR and PLR values and the onset of acute rejection of the transplanted organ [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing interest in better understanding of the indicators of inflammation, such as the neutrophil-to-lymphocyte ratio (NLR) [ 7 , 8 ], or platelet-to-lymphocyte ratio (PLR) which reflect the presence of systemic inflammation [ 9 ]. Both of them have been correlated with poor prognosis in a variety of conditions including end-stage kidney disease, heart disease or cancer [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%